INVESTIGATION OF HYDROGEN GAS PRODUCTION USING COPPER AND STAINLESS-STEEL ELECTRODES WITH VARIED ELECTRICAL CURRENT AND NaOH CATALYST CONCENTRATION : - - Hadi Susilo, Sugeng; Gumono, Gumono; Setiawan, Agus (Journal of Applied Engineering Science, 2023)
In recent years, the global energy demand, particularly the usage of fossil fuels as motor vehicle propellants such as gasoline and diesel, had steadily increased. This surge in consumption, alongside the burgeoning vehicle count, resulted in a depletion of petroleum reserves. Consequently, exploring alternative fuel sources became imperative. Hydrogen gas, derived from water through water electrolysis using an HHO generator, emerged as a promising alternative. This research investigated the impact of diverse copper and stainless-steel electrodes in varied electrolyte solutions and electrical currents for generating HHO gas. Employing an experimental methodology, the study modified an existing HHO generator, reassembling it with different materials based on the experimental design. Subsequent testing and data collection revealed that the highest flow rate of HHO gas, at 0.000807564 m3/s, occurred using stainless-steel electrodes with an electrical current of 50 A and a 50% NaOH concentration. The study concluded that the size of the electric current and the amount of NaOH significantly influenced the speed of HHO gas flow, indicating a direct relationship between these factors and gas production.